Demographic characteristics and their impact on satisfaction with antenatal care - Syafrudin Syafrudin; Yuliyanti Yuliyanti (Science Midwifery, 2025)
Introduction Satisfaction with antenatal care is an important indicator of the quality of care that supports maternal compliance in undergoing ANC examinations. The purpose of this study was to determine the effect of demographic characteristics on satisfaction with antenatal care at the Halmahera Health Center. Method An analytical observational design utilizing a cross-sectional approach was employed for this study. Data were collected through observations and questionnaires from 72 ANC patients. The analyzed variables included age, gestational age, education, income, parity, distance, occupation, and satisfaction with services. Logistic regression was used for data analysis to identify the factors that most significantly influence satisfaction with antenatal care. Results The findings revealed that 62 respondents (86%) expressed satisfaction with the services received. Age was found to have a significant effect on antenatal satisfaction (p = 0.004), as did education (p = 0.017) and occupation (p = 0.002). However, no significant relationship was found between gestational age (p = 0.966), parity (p = 0.195), distance (p = 0.607), or income (p = 0.104) and satisfaction with antenatal care. In conclusion, the factors of age, education, and occupation were identified as influential in determining patient satisfaction. It is recommended that the Halmahera Health Center adopt a more personalized service approach, tailor educational materials to various education levels, offer flexible services for working patients, and enhance communication across different age groups to improve overall satisfaction levels.